Investigating the impact of human resources development in achieving organizational agility in the urban water and sewage company of Ilam province - Taban, Mohammad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: If an organization wants to be successful and agile, it should firstly attract an efficient workforce and secondly pay special attention to their maintenance and development so that they will be more motivated to serve in the organization. Therefore, the current research was conducted to determine the impact of human resources development in achieving organizational agility in the urban water and sewage company of Ilam province. Methodology: In terms of purpose, the present research is applied, and in terms of method and descriptive nature, it is survey type. The statistical population in this research is managers, employees, and supervisors of different units at different organizational levels in the water and sewage company of Ilam province. The statistical population’s total size is 420 people (N = 420). The statistical sample size was 201 people using Morgan’s table. In this research, Tonke Nejad and Davari’s human resource development questionnaire (2018), with a reliability coefficient (0.87), and the organizational agility questionnaire by Sharifi and Zhang (1999), with a reliability coefficient (0.81) were used to collect data. In order to investigate the issue, one main hypothesis and seven sub-hypotheses were formulated, and Pearson’s correlation coefficient, linear regression and structural equation model were used to analyze the collected data. Results: The obtained results showed a positive and significant relationship between the components of human resource development (coherence, coordination, adaptation, identity, intellectual, attitudinal, and occupational) and organizational agility of the urban water and sewage company of Ilam province. Conclusion: There is a significant relationship between the development of human resources and the organizational agility of the urban water and sewage company of Ilam province.